Sentidos constituídos por um educador popular acerca de sua prática desenvolvida com adolescentes: uma análise sócio-Histórica - Naves, Flaviana Franco (2011)
This qualitative research has had as its main objective to analyze the meanings constructed by a professional popular educator about his educative practice developed with adolescents of the low social class. The epistemology and methodology adopted were the ones of the Sociohistorical Psychology evidencing the categories sense and meaning that are the central points of the research. The study s subject is a popular educator that works with adolescents of the lower social class. To conduct the research we used the semi-structured interview in the recurrent modality. Three interviews were carried out with the same subject to qualify the information. The analysis procedure was the Strategy of Analysis of Signification Nuclei presented by Aguiar; Ozella (2006) that aims at approaching de subject s meaning zones from the empirical data to their interpretation. The analysis resulted in five Meaning nuclei, and an analytical essay was developed from intranuclei to internuclei. Our analysis revealed, among other aspects, that de meanings constructed by the popular educator are related to his practice that intends to be a way of visualization and conduction of contrahegemony, the youth emancipation, social changes, and above all, a movement that becomes a changing praxis that can contribute to the construction of a fairer and solidary world